2009
DOI: 10.1111/j.1399-5448.2008.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the relationship between heart rate control and adiposity in young children: a cross-sectional study (EarlyBird 33)

Abstract: The data suggest early gender differences in predictors of cardiac autonomic control. Pubertal staging was not undertaken in this study, and we plan to evaluate this in future studies to further clarify these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
4
15
0
1
Order By: Relevance
“…The lack of association between PLR and HRV can be further corroborated by the different gender effect in PLR and HRV parameters. In agreement with a previous report by Krishnan et al (2009) in a large group of children of similar age range, our data showed that girls had a significantly higher heart rate than boys. A higher heart rate indicates stronger sympathetic influence .…”
Section: Discussionsupporting
confidence: 93%
“…The lack of association between PLR and HRV can be further corroborated by the different gender effect in PLR and HRV parameters. In agreement with a previous report by Krishnan et al (2009) in a large group of children of similar age range, our data showed that girls had a significantly higher heart rate than boys. A higher heart rate indicates stronger sympathetic influence .…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with a previous report by Krishnan et al (2009) in a large group of children of similar age range, our data showed that girls had a significantly higher heart rate than boys. A higher heart rate indicates stronger sympathetic influence (Malik et al 1996).…”
Section: Discussionsupporting
confidence: 93%
“…In the other study, girls (aged (9 ± 0.25) years) showed higher resting heart rate but HRV were not different between genders [25]. Our study also showed no difference between genders.…”
Section: Discussionsupporting
confidence: 51%